ASPECTS OF THE STUDY OF PRAGMATICS IN LINGUISTICS (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
The field of phonology in linguistics deals with the systematic organization of sounds within languages. This article delves into different facets of phonological research, emphasizing how sounds function both within individual languages and across languages globally. Key topics include the representation of phonemes, phonological rules and processes, the significance of distinctive features, and the interface between phonology and other linguistic domains like morphology and syntax. We begin by discussing foundational theories in phonology, including generative phonology and optimality theory. Following this, we examine phonological phenomena such as assimilation, dissimilation, syllable structure, stress patterns, and tone systems. The article also considers the impact of phonological research on understanding language acquisition, language evolution, and speech disorders. Additionally, we explore recent advances in experimental phonology and computational modeling. Ultimately, this article underscores the importance of phonology in linguistic research, highlighting its essential role in comprehending the sound patterns inherent to human language. Key words: phonology, phonemes, phonological rules, distinctive features, generative phonology, optimality theory, syllable structure, stress patterns, tone systems, experimental phonology